DYSTOCIA DUE TO FETAL ASCITES, ANASARCA AND MICROMELIA IN A BUFFALO - KUMAR, AJEET; SINGH, A K; DODDAGOUDAR, V G; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2010)
The present communication depicts a case of dystocia in buffalo due to multiple congenital abnormalities which include fetal ascites, anasarca and micromelia.
Keywords: Anasarca; Ascitis; Buffalo; Dystocia; Micromelia